Metaphyseal fracture healing in a sheep model of low turnover osteoporosis induced by hypothalamic–pituitary disconnection (HPD). Issue 11 (27th June 2013) - Bindl, Ronny; Oheim, Ralf; Pogoda, Pia; Beil, Frank Timo; Gruchenberg, Katharina; Reitmaier, Sandra; Wehner, Tim; Calcia, Enrico; Radermacher, Peter; Claes, Lutz; Amling, Michael; Ignatius, Anita
ABSTRACT We recently established a large animal model of osteoporosis in sheep using hypothalamic–pituitary disconnection (HPD). As central regulation is important for bone metabolism, HPD‐sheep develop severe osteoporosis because of low bone turnover. In this study we investigated metaphyseal fracture healing in HPD‐sheep. To elucidate potential pathomechanisms, we included a treatment group receiving thyroxine T4 and 17β‐estradiol. Because clinically osteoporotic fractures often occur in the bone metaphysis, HPD‐sheep and healthy controls received an osteotomy in the distal femoral condyle. Half of the HPD‐sheep were systemically treated with thyroxine T4 and 17β‐estradiol during the healing period. Fracture healing was evaluated after 8 weeks using pQCT, µCT, and histomorphometrical analysis. Bone mineral density (BMD) and bone volume/total volume (BV/TV) were considerably reduced by 30% and 36%, respectively, in the osteotomy gap of the HPD‐sheep compared to healthy sheep. Histomorphometry also revealed a decreased amount of newly formed bone (−29%) and some remaining cartilage in the HPD‐group, suggesting that HPD disturbed fracture healing. Thyroxine T4 and 17β‐estradiol substitution considerably improved bone healing in the HPD‐sheep. Our results indicate that fracture healing requires central regulation and that thyroxine T4 and 17β‐estradiol contribute to the complex pathomechanisms of delayed metaphyseal bone healing in HPD‐sheep. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:1851–1857, 2013